Motivasi Pelayanan Musik Remaja di Gereja IFGF Jakarta Menurut 1 Timotius 4:6-16 - Poroe, Herman; Pasaribu, Evinta Hotmarlina; Idayanti, Esther; Poli, Michael Jacky (STT Internasional Harvest Tangerang, 2024)
The church greatly needs the next generation to continue its mission, including in the area of music ministry. This ministry plays a crucial role in worship. However, not all teenagers have the enthusiasm to serve in music. Therefore, this paper seeks to identify the motivational factors in music ministry at IFGF Jakarta. Five (5) motivational indicators were identified: the desire to serve, understanding the basic principles of ministry, developing potential, exemplary leadership from spiritual leaders, and self-actualization through ministry. The research method used was a quantitative approach through surveys and a descriptive approach with literature studies. The study was conducted in 2024 among 70 teenagers at IFGF Jakarta. The results indicate that the teenagers are motivated for music ministry, with the dominant indicator being self-actualization through music ministry. Some reccomendations, to successfully motivate teenagers in music, it is necessary to develop a strategy, provide opportunities, and then guide them appropriately according to their individual gifts and talents.